WORK STRESS AND WORK PRODUCTIVITY WITH SELF ADJUSTMENT OF EMPLOYEES IN SOCIAL INSTITUTES DEVELOPMENT WORKS OF HARAPAN JAYA IN BALARAJA - Rilla Sovitriana; Wikrama Wardana; April Gunawan; Nuraeni Nuraeni; Poniah Juliawati; Rini Astuti (Sosiohumaniora, 2023)
Adjustment during work requires extra precision. With the process of self-adjustment, work productivity can be overcome so that it does not have an impact on pressure at work. The purpose of this study was to examine the relationship between work stress and work productivity with adjustment to employees at the Bina Karya Harapan Jaya Social Institution in Balaraja. The data collection method in this study used a quantitative method using a scale which included the independent variable, namely work stress and the dependent variable in this study, namely self-adjustment. The respondents used in this study were 31 PJLP employees of the Bina Karya Harapan Jaya Social Institution in Balaraja. Sampling in the research used is saturated sampling. Measuring tool used is the scale of work stress, work productivity, adjustments were analyzed using the SPSS application version 24.0 for Windows. The results showed that there was a significant relationship between work stress and self-adjustment, obtaining a correlation rx1y = -0.175 P = 0.347; P < 0.05 ; Ho accepted. Then between work productivity and self-adjustment obtained a correlation of rx2y = 0.206 P = 0.267; P < 0.05 ; Ho accepted. From the results of this study it can be concluded that overall work stress and work productivity with self-adjustment of employees are in the high category. Then between work productivity and self-adjustment obtained a correlation of rx2y = 0.206 P = 0.267; P < 0.05 ; Ho accepted. From the results of this study it can be concluded that overall work stress and work productivity with self-adjustment of employees are in the high category. Then between work productivity and selfadjustment obtained a correlation of rx2y = 0.206 P = 0.267; P < 0.05 ; Ho accepted. From the results of this study it can be concluded that overall work stress and work productivity with self-adjustment of employees are in the high category.